Fuzzy Logic Based Controller Design for a Typical Industrial Application Problem - T. C. Manjunath,; Pavithra G., Ravi Rayappa, Rajasekhar Koyyeda, Satvik M. Kusagur, Praveen N., Gopalaiah, Arun Kumar G., Spoorthi Jainar, (Journal of Electronic Design Engineering, 2020)
In this paper, the fuzzy logic-based controller design for a typical industrial application problem is presented in brief with the hardwired model of the designed unit. This paper includes the plan and execution of mechanized clothing in a firm. The clothing has a washtub having a limit of around 60 kgs. The plan consolidates exceptional equipment to peruse the information from sensors in the tub like-the cleanser ought to be added relying upon the soil and the heaviness of the garments detected from the tub; relying upon the heaviness of the material to be washed, the water must come in through the gulf consequently; the number of wash-cycles will likewise rely upon the earth and the weight; The earth level should be checked toward the finish of each cycle and if the soil is under an ideal worth the cycle should be ended naturally. A PC is to be utilized to play out the different figurings and to control and screen all the phases of the venture. The product is composed to computerize the activity utilizing the idea of fluffy rationale.